Performance Optimization of Solar Photovoltaic System using Parabolic Trough and Fresnel Mirror Solar Concentrator - Md. Abdullah Al Masud; Maruf Abedien; Afif Arafi; Md. Joynal Abadin; Md. Rafiqul Islam; Md. Shamimul Haque Choudhury (International Journal of Integrated Engineering, 2022)
An attempt has been taken to design parabolic trough and Fresnel mirror solar concentrator with the purpose of optimizing the output power of a photovoltaic system for both bright sunny day and cloudy day by using a 72-cell 5W photovoltaic solar panel. The PV system’s efficiency has been analyzed in terms of output voltage, current, and power of the solar panel. Accordingly to our expectation, we observed that on a bright sunny day, the output power improvement of the solar panel is 26.81% for the parabolic trough and 17.89% for the Fresnel mirror concentrator. On a cloudy day, both concentrators improve output power by 22.3% and 14.1%, respectively. In terms of power optimization of a photovoltaic system, the following has been discerned: a solar photovoltaic concentrator system with a parabolic trough is much more effective than one with a Fresnel mirror.